If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + 1 = 4t + -9 Reorder the terms: 1 + 8t = 4t + -9 Reorder the terms: 1 + 8t = -9 + 4t Solving 1 + 8t = -9 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 1 + 8t + -4t = -9 + 4t + -4t Combine like terms: 8t + -4t = 4t 1 + 4t = -9 + 4t + -4t Combine like terms: 4t + -4t = 0 1 + 4t = -9 + 0 1 + 4t = -9 Add '-1' to each side of the equation. 1 + -1 + 4t = -9 + -1 Combine like terms: 1 + -1 = 0 0 + 4t = -9 + -1 4t = -9 + -1 Combine like terms: -9 + -1 = -10 4t = -10 Divide each side by '4'. t = -2.5 Simplifying t = -2.5
| 1x-3=-5x+6 | | 2-3(m-1)=10-(9m+1) | | x^6=z | | 4(3x-6)-3=8(x+1)+7 | | 4a-6=8-(9+a) | | lnx=6.4385 | | 5[5+7]= | | 5+6[d+h]= | | 6a-1r=6 | | 10-w=285 | | 3y+1=5.2 | | -70+7=63 | | 4[d+f]= | | 0.625x-2=-12 | | 4/3(x-3)=8 | | 5x+7x-34=85-5x | | 8x+7=-3x-1 | | 2sin^2x-sinx+1=0 | | 9(z-913)=315 | | 21-5h=h+6 | | 13(-6x)+15=375 | | 14(t-910)=476 | | -5p+3=43 | | .80x+.20(70)=.70(70+x) | | .80x+.25(70)=.70(70+x) | | 4(s-859)=344 | | (x-2)=12(y-3) | | 2x+76=170 | | X+2y-7=6 | | (R/3)-4=11 | | x+2+x+4+x=180 | | 5x/3-2=13 |